Systematic Renewal in The Study of Hadith Terminology and Its Prospects | التجديد المنهجي في علم مصطلح الحديث وآفاق تحريره - Hakima Ahmed Hafidi (Al-Zahra : Journal for Islamic and Arabic Studies, 2020)
This topic deals with the issue of systematic renewal in the science of the term of the hadeeth, and on the prospects of its editing in terms of talking about the stages passed by the editing of this science, highlighting placements of renewal that characterized each stage from the previous in a studyThe research ends with a number of results, the most important of which, is the call to edit the issues of this science on the thematic units, and to strengthen the editing by examples , And applied models in each issue.